2012
DOI: 10.1111/evo.12022
|View full text |Cite
|
Sign up to set email alerts
|

The Maintenance of Sperm Variability: Context-Dependent Selection on Sperm Morphology in a Broadcast Spawning Invertebrate

Abstract: Why are sperm so variable despite having a singular, critical function and an intimate relationship with fitness? A key to understanding the evolution of sperm morphology is identifying which traits enable sperm to be successful fertilizers. Several sperm traits (e.g., tail length, overall size) are implicated in sperm performance, but the benefits of these traits are likely to be highly context dependent. Here, we examined phenotypic selection on sperm morphology of a broadcast spawning tube worm (Galeolaria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(53 citation statements)
references
References 88 publications
(136 reference statements)
5
47
1
Order By: Relevance
“…We did not conduct trials with sperm competition because we were interested in alternative mechanisms of sperm evolution and lacked the capacity to assign zygote paternity via molecular analyses. Free-spawned eggs in nature are often faced with sperm limitation [11,12], making our trials ecologically relevant to this mating system (see also [39,40]) but nonetheless limited to inferring selection pressures in the absence of competition. Trials were conducted in 13 replicate blocks with 5-11 males per block.…”
Section: (B) Manipulation Of Fertilization Environmentmentioning
confidence: 99%
“…We did not conduct trials with sperm competition because we were interested in alternative mechanisms of sperm evolution and lacked the capacity to assign zygote paternity via molecular analyses. Free-spawned eggs in nature are often faced with sperm limitation [11,12], making our trials ecologically relevant to this mating system (see also [39,40]) but nonetheless limited to inferring selection pressures in the absence of competition. Trials were conducted in 13 replicate blocks with 5-11 males per block.…”
Section: (B) Manipulation Of Fertilization Environmentmentioning
confidence: 99%
“…Nevertheless, sperm phenotype also covaries with the paternal phenotype or paternal environment, and it is this non-genetic variation that is relevant to this review. For example, non-genetic factors such as size, age and condition can vary with sperm morphology in some species but not others (Devigili et al, 2013;Johnson et al, 2013;Pitnick et al, 2008a;Rakitin et al, 1999;Schulte-Hostedde and Millar, 2004). Sperm morphology can also vary in time (Lüpold et al, 2012) and space Manier and Palumbi, 2008;Marks et al, 2008;Schmoll and Kleven, 2011).…”
Section: Reviewmentioning
confidence: 99%
“…More recently, however, there has been growing evidence that selection on sperm phenotype is context dependent, such that different phenotypes will be favoured under different conditions (Crean and Marshall, 2008;Fitzpatrick et al, 2007). For example, Johnson et al (Johnson et al, 2013) showed that when sperm were able to access eggs immediately, sperm with long tails and smaller heads were favoured, but when sperm accessed eggs after ageing, sperm with larger heads were favoured. Differential selection on sperm phenotypes under different conditions has, in some species at least, led to the evolution of gamete plasticity whereby males adaptively adjust the phenotype of their sperm in accordance with their local environment.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, gamete characteristics operating at the scale of a single cell have been shown to mediate population-and individual-level differences in reproduction Snook, 2005;Fitzpatrick et al, 2012;Fitzpatrick and Lüpold, 2014;Simpson et al, 2014;Levitan, 2000;van der Horst and Maree, 2014). Sea urchin males with faster sperm have greater fertilization success (Levitan, 2000) and, in low sperm concentration situations, marine tube worm sperm head length correlates with relative fitness (Johnson et al, 2013). Gamete recognition factors are also known to play a role in sperm competition and fertilization success (Swanson and Vacquier, 2002;Palumbi, 1999;Zigler et al, 2005).…”
Section: Introductionmentioning
confidence: 99%